Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Rapid assessments accurately identify threatened Australian flora under IUCN Red List Criteria after megafires - Tom Le Breton; Mark K.J. Ooi; Sylvia Hay; Joe Atkinson; Doug Bickerton; Stephanie Cerato; Richard J.P. Davies; Chantelle Doyle; Rachael Gallagher; Bettina Ignacio; David Keith; Mellissa McCallum; et al. (Biological Conservation, 2025)

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

Mitigation and conservation plant translocations: Do perspectives of practice, funding and success vary between sectors? - Chantelle A.T. Doyle; Georgia E. Garrard; Jen K. Martin; Mark K.J. Ooi (Biological Conservation, 2024)

Achieving conservation outcomes in plant mitigation translocations: the need for global standards - Chantelle A. T. Doyle; Thomas Abeli; Matthew A. Albrecht; Joe Bellis; Bruno Colas; Sarah E. Dalrymple; Andreas Ensslin; Jaime Espejo; Paul L. A. Erftemeijer; Margaux Julien; Wolfgang Lewandrowski; Hong Liu; et al. (Plant Ecology, 2023)
Many countries have legislation intended to limit or offset the impact of anthropogenic disturbance and development on threatened plants. Translocations are often integral to those mitigation policies. When translocation is used exclusively to mitigate development impacts, it is often termed a ‘mitigation translocation.’ However, both the terminology and processes vary regarding interpretation and application, resulting in inconsistent standards, often leading to poorly planned and implemented projects. These mitigation projects rarely achieve the intended ‘no net loss’ of protected species due to issues with timelines and procedures that result in the mortality of translocated individuals. Instead, such projects are often process driven, focused on meeting legislative requirements which enable the development to proceed, rather than meaningful attempts to minimise the ecological impact of developments and demonstrate conservation outcomes. Here, we propose to reframe mitigation translocations as conservation driven, ensuring best practice implementation and hence, a quantified no net loss for impacted species. These methods include redefining the term mitigation translocation to include conservation objectives and outlining issues associated with the mitigation translocation processes worldwide. We also nominate global standards of practice to which all proposals should adhere, to ensure each project follows a trajectory towards quantified success, with genuine impact mitigation. These proposed standards focus on building efficient translocation plans and improving governance to facilitate a transition from project centred to ecology-driven translocation. Employment of these standards is relevant to development proponents, government regulators, researchers, and translocation practitioners and will increase the likelihood of conservation gains within the mitigation translocation sector.

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Density-dependent winter survival of immatures in an irruptive raptor with pulsed breeding - Rebecca A. McCabe; Jean-François Therrien; Karen Wiebe; Gilles Gauthier; David Brinker; Scott Weidensaul; Donald Reid; Frank I. Doyle; Karl-Otto Jacobsen; Tomas Aarvak; Ingar Jostein Øien; Roar Solheim; et al. (Oecologia, 2022)

Preparing threatened plants for translocation: does home soil addition and nutrient loading improve growth and flowering? - Chantelle A. T. Doyle; Belinda J. Pellow; Ross A. Rapmund; Mark K. J. Ooi (Plant Ecology, 2021)

Elevated rates of mild cognitive impairment in HIV disease - David P. Sheppard; Jennifer E. Iudicello; Mark W. Bondi; Katie L. Doyle; Erin E. Morgan; Paul J. Massman; Paul E. Gilbert; Steven Paul Woods (Journal of NeuroVirology, 2015)

Transatlantic migration by post-breeding puffins: a strategy to exploit a temporarily abundant food resource? - Mark J. Jessopp; Michelle Cronin; Thomas K. Doyle; Mark Wilson; Abigail McQuatters-Gollop; Stephen Newton; Richard A. Phillips (Marine Biology, 2013)

Altered tissue behavior of a non-aneurysmal descending thoracic aorta in the mouse model of Marfan syndrome - Darren Haskett; Jefferson J. Doyle; Connie Gard; Hwudaurw Chen; Corbie Ball; Mark A. Estabrook; Alejandra C. Encinas; Harry C. Dietz; Urs Utzinger; Jonathan P. Vande Geest; Mohamad Azhar (Cell and Tissue Research, 2012)

Responses to iron limitation in two colonies of Stylophora pistillata exposed to high temperature: Implications for coral bleaching - J. Malcolm Shick; Katrina Iglic; Mark L. Wells; Charles G. Trick; Jason Doyle; Walter C. Dunlap (Limnology and Oceanography, 2011)
Exposing the coral Stylophora pistillata to seawater depleted in available iron by complexation with the strong chelator desferrioxamine B reduces the photosynthetic efficiency and alters the pigment composition in its symbiotic algae at high temperatures. Similar effects of iron limitation are known for free‐living algae, but this is the first demonstration of low‐iron stress in a dinoflagellate living endosymbiotically. Maintaining corals at elevated temperature (30°C and 31°C) under diminished iron availability leads to reduced maximum quantum yields ( F v : F m ) of photosystem II (PSII), specifically on brightly illuminated surfaces of the coral. This reduction in maximum quantum yield is due in part to increased photoprotection, indicated by an increase in the photoprotective xanthophyll diatoxanthin, which promotes nonphotochemical quenching of excess light energy to restrict oxidative damage under conditions that impair photosynthetic electron transfer. However, photophysiological changes associated with the lowered maximum quantum yield did not prevent photodamage to PSII under the combined effects of elevated temperature and low iron availability, as shown by the decrease in maximum ( F m ) that was not accompanied by significant change in the minimum ( F o ) fluorescence yield. All of the foregoing is consistent with the potential of iron limitation to contribute to the underlying conditions by which thermal stress evokes the physiological response by corals that culminates in the symbiotic dysfunction of natural bleaching.

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 2—Investigation of Bias in Extra-Fine Mass Fraction with AIM-HRT Impactor - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 1 - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Natural Variation of Flowering Time and Vernalization Responsiveness in Brachypodium distachyon - Christopher J. Schwartz; Mark R. Doyle; Antonio J. Manzaneda; Pedro J. Rey; Thomas Mitchell-Olds; Richard M. Amasino (BioEnergy Research, 2010)

The Multi-Sensor Improved Sea Surface Temperature (MISST) Project - Chelle Gentemann; Peter Minnett; Joseph Sienkiewicz; Mark DeMaria; James Cummings; Yi Jin; James Doyle; Lew Gramer; Charlie Barron; Kenneth Casey; Craig Donlon (Oceanography, 2009)

Extension of Rapid Phase-Contrast Magnetic Resonance Imaging Using BRISK in Multidirectional Flow - Bradley L. Hershey; Mark Doyle; Eduardo Kortright; Rohan More; Geetha Rayarao; Andreas Anayiotos (Annals of Biomedical Engineering, 2005)

Aerodynamic particle size analysis of aerosols from pressurized metered-dose inhalers: Comparison of andersen 8-stage cascade impactor, next generation pharmaceutical impactor, and model 3321 aerodynamic particle sizer aerosol spectrometer - Jolyon P. Mitchell; Mark W. Nagel; Kimberly J. Wiersema; Cathy C. Doyle (AAPS PharmSciTech, 2003)

Fire Danger Monitoring Using ERS-1 SAR Images in the Case of Northern Boreal Forests - Brigitte Leblon; Eric Kasischke; Marty Alexander; Mark Doyle; Melissa Abbott (Natural Hazards, 2002)

Validation of Rapid Velocity Encoded Cine Imaging of a Dynamically Complex Flow Field Using Turbo Block Regional Interpolation Scheme for k Space - Eduardo Kortright; Mark Doyle; Andreas S. Anayiotos; Edward G. Walsh; Anthon R. Fuisz; Gerald M. Pohost (Annals of Biomedical Engineering, 2001)